BIOMEKANIKA OLAHRAGA PADA PENGEMBANGAN MOTORIK ANAK USIA PENDIDIKAN DASAR - Soetjipto, (Pendidikan Dasar, 2010)
Abstract; This study aims at 1) introducing how to use Dartfish program in measuring skill development, 2) measuring quantitatively the child motoric learning development in making short serve in badminton playing, 3) finding out the skill level of the short serve made by 10 13 year old badminton players. The result shows that their skill development in making short serve is still below standard eventhough they have been trained using feedback technique. The total rate of shuttlecock crossing over the net is 0.236 m.